IMPLEMENTASI PROGRAM KELURAHAN HEBAT DALAM PELAYANAN PUBLIK DI KELURAHAN PACEDA KECAMATAN MADIDIR KOTA BITUNG - RYCKI IMANUEL YOSEPH KANSIL; JOYCE RARES; RULLY MAMBO (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study is to find out the implementation of great urban village policies in public services in Bitung City. Qualitative research methods are also called naturalistic methods. For the results of this study, it can be seen that the policy standards for implementing the great village policy in Paceda Village have met the effectiveness criteria. And also this Great Kelurahan policy can be considered realistic to solve service problems so far because the service process provided is faster, transparent and uncomplicated and the standard of service provided is also easy for the public to access. The suggestions from the researchers are related to several problems in the application in the field where people who do not have cellphones/gadgets can coordinate with the head of the RT or head of the environment in the process of managing files via online in accordance with the policies of the Great Village.Â Keyword: Implementasion, Policy, Village, Public Sevice